2023
DOI: 10.1109/mnet.123.2100773
|View full text |Cite
|
Sign up to set email alerts
|

Graph Neural Networks for Communication Networks: Context, Use Cases and Opportunities

Abstract: Graph neural networks (GNN) have shown outstanding applications in fields where data is essentially represented as graphs (e.g., chemistry, biology, recommendation systems). In this vein, communication networks comprise many fundamental components that are naturally represented in a graph-structured manner (e.g., topology, routing, signal interference). This position article presents GNNs as a fundamental tool for modeling, control and management of communication networks. GNNs represent a new generation of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The graph-structured topology of wireless network enables the successful usage of GNN to solve a broad range of design problems over the wireless networks [80]. As a specialized NN for graph-structured data, GNN can exploit the domain knowledge of various applications to achieve near-optimal learning performance with good scalability and generalizability.…”
Section: Graph Neural Network For Structured Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The graph-structured topology of wireless network enables the successful usage of GNN to solve a broad range of design problems over the wireless networks [80]. As a specialized NN for graph-structured data, GNN can exploit the domain knowledge of various applications to achieve near-optimal learning performance with good scalability and generalizability.…”
Section: Graph Neural Network For Structured Optimizationmentioning
confidence: 99%
“…First, the permutation invariance and permutation equivariance properties of GNNs enable the learned NN to adapt to large-scale and dynamic scenarios by exploiting the analogies or equivalent patterns between the training network topology and dynamic testing conditions automatically. Second, GNNs leverage the distributed message passing architecture to learn local relationships among graph nodes and combinatorial generalization over graphs [80]. As a result, GNNs can generalize to large-scale communication networks with varying sizes and permuted structures (e.g., more users, antennas, BSs, etc.…”
Section: G Advantages and Disadvantagesmentioning
confidence: 99%
“…In line with previous research [33], such generalisation was not observed in terms of topology: Te agent trained in the NFSNet topology did not perform well in the COST 239 topology and vice versa. Studying the beneft of using Graph Neural Networks to overcome the lack of topology generalisation is part of current research [63].…”
Section: Trpo Agent Vs Heuristic: Blocking Performancementioning
confidence: 99%
“…GNNs are a subclass of DL models specifically designed to work on graph-structured data [2], and have been successfully applied to many different fields, including chemistry, biology, or computer vision [23]. In the field of communication networks, GNNs have been applied to a variety of tasks [17], such as routing optimization [15], power control in wireless networks [16], Distributed Denial of Service (DDoS) attack detection [12], or network intrusion detection [13].…”
Section: Related Workmentioning
confidence: 99%